Knowledge transfer and international joint ventures: the case of NUMMI and General Motors - Inkpen, Andrew C. (Strategic Management Journal, 2007)
Abstract Using a case study of NUMMI, a joint venture between General Motors (GM) and Toyota, this research note examines alliances and knowledge transfer with a focus on the organizational processes used to transfer knowledge. The results suggest two possible explanations for the knowledge transfer outcome. The primary explanation is that the systematic implementation of knowledge transfer mechanisms can overcome the stickiness and causal ambiguity of new knowledge. A second explanation is that creating successful knowledge transfer should be viewed from a change management perspective in which trial and error learning experiences and experimentation support the transfer outcome. Copyright © 2007 John Wiley & Sons, Ltd.